A Propensity Score–matched Analysis of Clinical Outcomes Between Single-level and Multilevel Intervertebral Decompression for Cervical Radiculopathy. Issue 4 (15th February 2023) - Oshina, Masahito; Kawamura, Naohiro; Hara, Nobuhiro; Higashikawa, Akiro; Ono, Takashi; Takeshita, Yujiro; Azuma, Seiichi; Fukushima, Masayoshi; Iwai, Hiroki; Kaneko, Takeshi; Inanami, Hirohiko; Oshima, Yasushi
Abstract : Study Design: Retrospective multicenter study with propensity score matching. Objective: To compare the clinical outcomes of single-level and multilevel intervertebral decompression for cervical degenerative radiculopathy. Summary of Background Data: In patients with cervical radiculopathy, physical examination findings are sometimes inconsistent with imaging data. Multilevel decompression may be necessary for multiple foraminal stenosis. Additional decompression is more invasive yet expected to comprehensively decompress all suspected nerve root compression areas. However, the surgical outcomes of this approach compared with that of single-level decompression remain unknown. Materials and Methods: The data of patients with spinal surgery for pure cervical radiculopathy were collected. Patients were categorized into the single-level (SLDG) or multilevel (MLDG) intervertebral decompression group at C3/C4/C5/C6/C7/T1. Demographic data and patient-reported outcome scores, including the Neck Disability Index (NDI) and Numerical Rating Scale (NRS) scores for pain and numbness in the neck, upper back, and arms, were collected. The NDI improvement rates and changes in NRS scores were analyzed one year postoperatively at patient-reported outcome evaluation. Propensity score matching was performed to compare both groups after adjusting for baseline characteristics, including the preoperative NDI and NRS scores. Results: Among the 357 patients in this study, SLDG and MLDG comprised 231 and 126 patients, respectively. Two groups (n=112, each) were created by propensity score matching. Compared with the MLDG, the SLDG had a higher postoperative NDI improvement rate ( P =0.029) and lower postoperative arm numbness NRS score ( P =0.037). Other outcomes tended to be more favorable in the SLDG than in the MLDG, yet no statistical significance was detected. Conclusions: In patients with cervical radiculopathy, the surgical outcomes of the SLDG showed better improvement in clinical outcomes than those of the MLDG. Numbness remained on the distal (arms) rather than the central (neck and upper back) areas in patients receiving multilevel decompression.